Multicenter electron-sharing σ-bonding in the AgFe(CO)4− complex. Issue 43 (21st October 2020) - Liu, Zhiling; Bai, Yan; Li, Ya; He, Jing; Lin, Qingyang; Hou, Lina; Wu, Hai-Shun; Zhang, Fuqiang; Jia, Jianfeng; Xie, Hua; Tang, Zichao
Abstract : For the AgFe(CO)4 − anion, the silver atom is covalently bonded to the anionic tetracarbonyl-iron, an isolobal analogue of the methyl radical, via a peculiar decentralized electron-sharing σ bond. Abstract : The heterodinuclear silver tetracarbonyl-iron anion was generated in the gas phase and studied by joint photoelectron velocity map imaging spectroscopy and quantum chemical calculations. The AgFe(CO)4 − anion is characterized to be an 18-electron complex with the silver atom covalently bonded to the anionic tetracarbonyl-iron, an isolobal analogue of the methyl radical. The bonding analyses using a range of state-of-the-art quantum chemistry methods revealed a peculiar decentralized bonding situation, where the silver atom is covalently bonded to both the iron center and the vicinal carbon atoms in the form of an electron-sharing σ bond.